Defining Measures in a Mereological Space (an exploratory paper) - Barbieri, Giuseppina; Gerla, Giangiacomo (Logic and Logical Philosophy, 2021)
We explore the notion of a measure in a mereological structure and we deal with the difficulties arising. We show that measure theory on connection spaces is closely related to measure theory on the class of ortholattices and we present an approach akin to Dempster’s and Shafer’s. Finally, the paper contains some suggestions for further research.